Ouvertures critiques - Lionel Jacquot (La Nouvelle Revue du Travail)
Concluding this edition of Controversy, Lionel Jacquot revisits four of the contributions and debates the critical perspectives of work upon which they rely. He starts by linking the programmes to one another to construct an ideal-type in which the sociology of work can serve as a critical science. He then shows how perspectives and problems relating to this ideal-type can be used to revive such critique. Lastly, he highlights the plurivalence of critical acts.